(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. Hepcidin is a key regulator of iron homeostasis, takes part in pathophysiology of anemia and cardiovascular disease in maintenance hemodialysis (MHD) patients. The aim of this study was to compare the effect of glucose-free and glucose-containing dialysate on the clearance of hepcidin-25 during a hemodialysis (HD) session and discuss its potential mechanism in MHD patients. Methods. In a longitudinal interventional study of 30 stable MHD patients without diabetes, we measured serum hepcidin-25 and plasma catecholamines (adrenaline, noradrenaline, and dopamine) during HD session using glucose-free dialysate and then switched to 5.55 mmol/L glucose-containing dialysate. One-way analysis of variance (ANOVA) was used to identify the effect of two dialysates on the intra-dialysis changes of hepcidin-25 and catecholamines. Spearman and Pearson correlation coefficients were performed to detect the relationships between hepcidin-25 and catecholamines. Results. Glucose-free dialysate achieved a greater reduction of hepcidin-25 than 5.55 mmol/L glucose-containing dialysate in a single bicarbonate HD session [-8.43 (-15.44 to -1.42) vs. 0.46 (-6.09 to 7.00) %, P < .05]. The intra-dialysis changes of catecholamines showed no significant differences between the two dialysates. The serum hepcidin-25 levels were positively associated with plasma catecholamines levels at pre-, intra- and post-HD (R = 0.22 0.62 with P < .05). Conclusions. Our findings suggest that glucose-containing dialysate might up-regulate hepcidin-25 synthesis through activation of the sympathetic nervous system or oxidative stress, possibly mediated by increased production of catecholamines. Adequately designed studies are needed to confirm and reveal the mechanisms of dialysate glucose concentration on hepcidin-25 kinetics during HD sessions.